HUBUNGAN PENGETAHUAN DENGAN TINGKAT KECEMASAN IBU PERIMENOPAUSE DALAM MENGHADAPI MENOPAUSE DI PUSKESMAS BATANGTORU TAHUN 2020 - RAHMAH JULIANI SIREGAR (JURNAL ILMIAH SIMANTEK, 2021)
Menopause is a natural process that every woman experiences. But for some women, menopause is the saddest time in life.There are many concerns that envelop the woman's mind when entering this phase. Many mothers who go throughmenopause become easily anxious people. This anxiety arises as a result of frequent haunting worries in the face ofsituations they have never previously worried about. The purpose of this study is to find out the relationship of knowledgewith the level of anxiety of the perimenopause mother in the face of menopause at the Batangtoru Health Center inPadangsidimpuan City in 2020. The research design that will be used in this study is a correlational research design thataims to get an idea of the relationship between two or more research variables. The number of samples in this study was 40people. Sampling is done purposively samples. This research was conducted at Batngtoru Health Center. Data analysis isdone with chi-square. The results of the chi-square statistic test obtained there is a link between knowledge and anxietylevels of the perimenopause mother in the face of menopause (value p=0.004).